2023
DOI: 10.17776/csj.1317923
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antimicrobial and Antioxidant Activities of some Lichens

Dilek Us,
Ayşe Kara,
Elif Ünal
et al.

Abstract: This study investigated the antimicrobial and antioxidant properties of methanol extracts from five lichen species: Polycauliona candelaria (Syn. Xanthoria candelaria), Nephromopsis chlorophylla (Syn. Cetraria chlorophylla), Circinaria calcarea (Syn. Aspicilia calcarea), Bryoria capillaris (Syn. Alectoria cana), and Peltigera canina (Syn. Dermatodea canina). Antimicrobial activities were determined using the agar disc diffusion method, while minimal inhibitory concentration (MIC) values were determined using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to Kello et al, DPPH radical scavenging activities of lichen methanolic extracts increased proportionately with concentration. Absorbance values of these extracts and standard antioxidants were assessed at 24.75 µg/mL [9,12]. Further, Tartouga et al, the extract demonstrated a 38.39% inhibition of BSA denaturation at a concentration of 1000 µg/mL [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Kello et al, DPPH radical scavenging activities of lichen methanolic extracts increased proportionately with concentration. Absorbance values of these extracts and standard antioxidants were assessed at 24.75 µg/mL [9,12]. Further, Tartouga et al, the extract demonstrated a 38.39% inhibition of BSA denaturation at a concentration of 1000 µg/mL [23].…”
Section: Discussionmentioning
confidence: 99%
“…C. calcarea, N. chlorophylla, and B. capillaris showed significant effectiveness against B. cereus, B. subtilis, C. perfringens, and E. coli, resulting in ZOI ranging from 9 to 15 mm. In a study conducted by Us et al, it was shown that C. calcarea exhibited the most activity, resulting in a 15 mm inhibition zone against both E. coli and B. cereus [12]. The study assessed the antibacterial efficacy of solvent extracts derived from 12 lichen species against pathogenic bacteria (P. aeruginosa, E. coli, S. aureus, and K.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations